TERMS FOR ADOPTIVE PARENTS AND ADOPTIVE CHILDREN IN ARKHANGELSK DIALECTS - Ирина Борисовна Качинская (Irina B. Kachinskaya) (Вестник Пермского университета. Российская и зарубежная филология, 2017)
Lexemes denoting adoptive parents and adoptive children – stepfather, stepmother, stepson, stepdaughter, stepsibling – refer to the notion “adoptive relationship”. Close to this group are those lexemes which name orphans and also children and adults who were taken to one’s home as helpers and inherited property later on. The article deals with the terms used to name adoptive parents and children or to address them. Forms of address, as a rule, involve terms of consanguinity. Both separate terms and combinations can be found. Motivation for the terms with the meaning “adoptive children” is also shown. As a rule, the inventory of terms of any lexical-semantic group is much more abundant in dialects than in literary language, primarily due to word-forming and also semantic derivation. However, this also concerns terms of adoptive relationship. These terms presuppose metaphoric transfer to the botanical field (e. g. mat’-i-macheha (foalfoot, in literal translation – mother-and-stepmother) is known to have offshoots called pasynki (stepsons)). Examples of metaphoric transfer in dialects are much more numerous, they relate not only to the botanical field but also to the zoological one and are used in the objective and abstract spheres. Macheha (stepmother) and pasynok (stepson) tend to develop transferred meanings more often than other lexemes. In the article, terms of adoptive kinship in their direct and transferred meanings are considered, Arkhangelsk dialects being the case study.